The process of judicial filiation of extramarital paternity and its evolution over time - Fernández Yábar, Rocío Isabel (2020)
In the present article, the author addresses the various changes that have been taking place regarding the Process of Judicial Affiliation of Extramarital Paternity in recent years, analyzing whether these have been positive or not, especially for children and adolescents born outside of a marriage. Highlighting the most relevant news that each one of the modifications brought.